2000
DOI: 10.4049/jimmunol.165.7.3839
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Identification of C3d Residues Essential for Its Binding to Complement Receptor 2 (CD21)

Abstract: A vital role for complement in adaptive humoral immunity is now beyond dispute. The crucial interaction is that between B cell and follicular dendritic cell-resident complement receptor 2 (CR2, CD21) and its Ag-associated ligands iC3b and C3dg, where the latter have been deposited as a result of classical pathway activation. Despite the obvious importance of this interaction, the location of a CR2 binding site within C3d, a proteolytic limit fragment of C3dg retaining CR2 binding activity, has not been firmly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
117
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(131 citation statements)
references
References 48 publications
12
117
2
Order By: Relevance
“…In contrast to the emerging consensus regarding the CR2 side of the CR2-C3d interface, it is still uncertain where CR2 binds C3d (33,36,55). Our data do not directly address this question but are consistent with the co-crystal structure determination showing the SCR2-C3d interaction.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to the emerging consensus regarding the CR2 side of the CR2-C3d interface, it is still uncertain where CR2 binds C3d (33,36,55). Our data do not directly address this question but are consistent with the co-crystal structure determination showing the SCR2-C3d interaction.…”
Section: Discussionsupporting
confidence: 74%
“…It has been recognized in a number of studies that C3d-CR2 association is pH-and ionic strength-dependent (20,(33)(34)(35)(36). Similar pH and ionic strength dependence was also observed in the homologous interaction between C4b and C4-binding protein (37,38).…”
supporting
confidence: 50%
“…The structure of free C3d became first available and revealed the presence of an acidic pocket that was thought to be a candidate for the association site with CR2 (39). Subsequent mutagenesis studies within the acidic pocket of C3d in iC3b demonstrated either loss or gain of binding ability to CR2(SCR1-15)-bearing Raji cells and supported this hypothesis (35). However, the structure of the C3d-CR2(SCR1-2) complex became available later, showing that the association site was not at, or close to, the acidic pocket (35).…”
mentioning
confidence: 53%
“…This provides a link between the innate and the adaptive immune system (Carroll, 2004). Multiple studies have been performed on the interaction of CR2 with iC3b and C3dg (Clemenza and Isenman, 2000;Diefenbach and Isenman, 1995;Esparza et al, 1991;Kalli et al, 1991;Lambris et al, 1985;Lowell et al, 1989;Molina et al, 1995;Morikis and Lambris, 2004;Sarrias et al, 2001) (Fig. 2).…”
Section: C3b Fragments Signalingmentioning
confidence: 99%